LEXICAL BUNDLES IN JOURNAL ARTICLES ACROSS ACADEMIC DISCIPLINES - Kwary, Deny Arnos; Ratri, Dewantoro; Artha, Almira F. (Universitas Pendidikan Indonesia, 2017)
This study focuses on the use of lexical bundles (LBs), their structural forms, and their functional classifications in journal articles of four academic disciplines: Health sciences, Life sciences, Physical sciences, and Social sciences. The corpus comprises 2,937,431 words derived from 400 journal articles which were equally distributed in the four disciplines. The results show that Physical sciences feature the most number of lexical bundles, while Health sciences comprise the least. When we pair-up the disciplines, we found that Physical sciences and Social sciences shared the most number of LBs. We also found that there were no LBs shared between Health sciences and Physical sciences, and neither between Health sciences and Social sciences. For the distribution of the structural forms, we found that the prepositional-based and the verb-based bundles were the most frequent forms (each of them accounts for 37.1% of the LBs, making a total of 74.2%). Within the verb-based bundles, the passive form can be found in 12 out of 23 LB types. Finally, for the functional classifications, the number of referential expressions (40 LBs) is a lot higher than those of discourse organizers (12 LBs) and stance expressions (10 LBs). The high frequency of LBs in the referential expressions can be related to the needs to refer to theories, concepts, data and findings of the study.